Study of Ethnoveterinary Medicinal Plants Used by Pastoralists in Northern Gombe State, Nigeria (Asian Journal of Plant Biology, 2021)
Ethnoveterinary is the total of all practices that enable man to prevent his livestock from diseases, alleviate and relieve suffering to bring about healing, and increase the production and productivity of livestock within a minimum cost. Overutilization, overexploitation, deforestation for fuelwood, and farmland expansion expose some of the plants to threaten. The study was carried out in three randomly selected districts in Northern Gombe State, Nigeria. Among all, 80% of the respondents are male among which 56% are 35 years and above. 43 plants were reported used as ethnoveterinary plants in the area (oral interview) among which only 28 were found to be present in the field (field assessment). Guiera senegalensis is the most abundant plant (7.85%) followed by Piliostigma reticulatum (7.23%), Combretum collinum and Detarium microcarpum (3.00% both). Fabaceae is the most abundant family (30.85%) of the identified plants followed by Combretaceae (15.25%). Plant bark is the most common part used in curing and preventing animals from diseases which subject some of the plants (Burkia africana) to nearly endangered states. 28 plant samples were collected, identified, pressed, and laid in Botany Department Herbarium, Gombe State University, among these, 2 plant samples were not successfully identified. It is recommended that regulatory bodies should be empowered to check the uncontrolled deforestation occurring in the area
Keywords: Ethnoveterinary, Pastoralists, Gombe-Abba, Deforestation, Diversity